Factors Shaping Student Debt Attitudes and Behaviours: A Systematic Review and a Pilot Qualitative Study at an Indonesian Multicultural University - Ashri Rahadi; Deddy Priatmodjo Koesrindartoto; Anggara Wisesa (Research Synergy Foundation, 2024)
The growing concern over student debt highlights its impact on both individual students and the broader economy. Investigating debt attitudes offers insights into an individual’s predisposition to incur debt, influencing debt levels, repayment discipline, and potential behavior modifications through education. This study employed a thematic analysis conducted using systematically selected literature from global databases to understand factors aligned with various debt attitude spectrums. Four global themes were identified: (I) Personal factors, (II) Social factors, and (III) Behavioral Factors as factors correlated with anti- and pro- debt attitudes and behavior. This research presents a global framework for understanding debt attitudes across diverse factors, which is adaptable to specific cultural contexts. Student debt is a complex issue. To fully understand it, we need to examine a broad range of factors, encompassing not only personal and behavioral aspects but also social perspectives. In addition, certain factors may hold greater significance depending on the context. Practical recommendations are offered for educators and policymakers as considerations for addressing debt.